Factors affecting uptake of antenatal HIV testing in London: results of a multicentre study. - Gibb, D. M. (BMJ Group, 1998)
OBJECTIVES: To measure the uptake of antenatal HIV testing and determine its relation to risk of HIV and to screening practices. DESIGN: Multicentre prospective questionnaire study. SUBJECTS: Pregnant women attending six maternity units. SETTING: Inner London, 1995-6. MAIN OUTCOME MEASURES: Uptake of testing by risk factors for HIV, ethnicity, and factors about the antenatal interview. RESULTS: All units had a "universal offer" policy for HIV testing. In five units forms were completed for 18,791 (88%) of 21,247 pregnant women. The sixth unit, where the response rate was too low to assess uptake, was excluded from the analysis. Uptake ranged from 3.4% to 51.2% (overall 22.9%), in parallel with detection of previously undiagnosed infection in pregnant women (4.9-60%). Controlling for unit, uptake was higher among the 7% who disclosed risk factors. Among those at low risk, uptake varied by ethnic group (South Asian women 9%; Latin American and Mediterranean women 33%). The relation between uptake and HIV risk category varied greatly across units. Despite increased HIV seroprevalence in black African women, uptake was similar in this group to that among women at low risk (24%). Uptake increased 2.1-fold if HIV transmission was discussed. Midwives reported spending 7 (2-15) minutes discussing HIV issues. CONCLUSIONS: Uptake of HIV testing was unacceptably low in all units, with maternity unit the strongest predictor. New approaches to antenatal HIV testing are urgently required and uptake should be audited routinely.